2015
DOI: 10.2355/isijinternational.55.775
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Steel/Slag/Submerged Entry Nozzle and its Impact on Refractory Wear – Thermochemical Process Simulation

Abstract: This work presents the generation and application of a process model which aims to increase the understanding of submerged entry nozzle (SEN) wear during continuous casting and its dependence on steel and slag compositions. An effective equilibrium reaction zone model was built and applied to calculate the equilibrium compositions of steel and slag at their common interface and in contact with the SEN. The results allow the estimation of the interface tension gradient responsible for Marangoni convection. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Annular corrosion grooves can be clearly observed at the slag line for both refractories, indicating strong interaction between the refractory and slag during casting. 13 Kumar et al 34 also found that the corrosion depth of casting mould flux and the dissolution of alumina increased with graphite content in the refractory. However, these two values were only 7.8 and 10.0 mm, respectively, for the low coarse cracks, or bends), confirming the active roles of graphite and SiC whiskers in high-temperature mechanical strength and thermal shock resistance.…”
Section: Industrial Trialmentioning
confidence: 96%
See 2 more Smart Citations
“…Annular corrosion grooves can be clearly observed at the slag line for both refractories, indicating strong interaction between the refractory and slag during casting. 13 Kumar et al 34 also found that the corrosion depth of casting mould flux and the dissolution of alumina increased with graphite content in the refractory. However, these two values were only 7.8 and 10.0 mm, respectively, for the low coarse cracks, or bends), confirming the active roles of graphite and SiC whiskers in high-temperature mechanical strength and thermal shock resistance.…”
Section: Industrial Trialmentioning
confidence: 96%
“…Figure 8 shows the photographs of the longitudinal sections of the two SENs after working for 8 hours. 13 was detected at the interface, indicating that the indirect oxidation of graphite also occurred by reducing Fe 2 O 3 . The maximum depth of the corrosion groove on the left and right side of the traditional Al 2 O 3 -C refractory were 13.6 and 11.0 mm, respectively.…”
Section: Industrial Trialmentioning
confidence: 98%
See 1 more Smart Citation
“…Viscosity is one of the most important properties of mold flux as it determines the powder consumption and therefore the lubrication of the shell; [1,2] it also affects the formation of the slag rim in the vicinity of the meniscus, [3] the slag entrapment, [4] as well as the erosion of the nozzle. [5] Early models for predicting the viscosity of mold flux were developed by using viscosity measurements that spanned relatively small ranges of temperature and viscosity. The data, derived from these restricted ranges of experimental conditions, were generally linear in reciprocal of temperatures; thus, the early models follow Arrhenius formulation strictly.…”
Section: Lejun Zhou and Wanlin Wangmentioning
confidence: 99%
“…[5] Early models for predicting the viscosity of mold flux were developed by using viscosity measurements that spanned relatively small ranges of temperature and viscosity. The data, derived from these restricted ranges of experimental conditions, were generally linear in reciprocal of temperatures; thus, the early models follow Arrhenius formulation strictly.…”
mentioning
confidence: 99%